EFFECTS OF SAND MINING ON CORAL REEFS IN RIAU ISLANDS - Supriharyono . (JOURNAL OF COASTAL DEVELOPMENT, 2004)
Effects of sand mining on coral reefs have been carried out in Riau Islands, from September to November 2003. The study used was explorative method, while the data were collected both primary through field observation and interview and secondary data obtained from related institutions. The results showed that the reefs were in moderate to good conditions. Majority of the moderate conditions were found in the deeper water (10 m depth). Similarly, the percentage of living coral cover was also lower in the deeper water compared to the shallow one (3 m). It is believed that this may due to light transparency. However, it is too early to say that the lower of light transparency in the depth 10 m is due to sand mining activities. In addition, the fishing capture production was significantly decreased after sand mining becoming intensive in study sites during autonomy era.